Public Manajemen Servicc Policy Healtt Services In The City Of Palu, Central Sulawesi - Idham, Idham (Publisher Cv. Inara Colaboration with www.stie-sampit.ac.id, 2024)
Determination of the target of disease sufferers is determined by the regional head using the latest basic health research data determined by the Minister of Health (Palu City Health Office, 2022). Aspects of the carrying capacity of the implementation organization, the application of policies has not been going well because community constraints are not compliant with the treatment that causes lack of control of diseases suffered. The development of theory through case studies, is one of the research strategies involving one creating theoretical construction, proposition or theory of the middle range based on cases and empirical facts (Eisenhardt, 1989). Organizing SPM, the Minister of Domestic Affairs of the Republic of Indonesia issued Regulation Number 59 of 2021 concerning the application of minimum service standards then this circular is a reference to the local government to be able to issue a Governor Regulation on the Application of the Minimum Service Standards for 2023 issued on May 24, 2023 where the implementation of the application Minimum service standards include the type and quality of basic services starting from the application, monitoring, evalaution, handling issues and problems in the application of minimum service standards in the regions as regulated in the provisions of Governor Regulation Number 23 of 2022 concerning the application of Minimum Service Standards (Pergub, 2023). Aspects of the carrying capacity of the implementing organization, the application of this policy has not been going well because of the existence of several obstacles such as there are still people who are not compliant with anti -hypertensive treatment that causes lack of blood pressure control. Judging from the aspect of the carrying capacity of the implementation organization, the application of this policy has not been well going well in the Puskesmas in the Palu coat, due to several obstacles such as there are still people who are not compliant with anti -hypertension treatment that causes lack of disease control.